PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA PT. PERKEBUNAN NUSANTARA IV REGIONAL 1 - Bella Wasistha Matanari; Retnawati Siregar; Ali Usman (EKSPOLHUM, 2024)
This study aims to find out the report on the realization This research aims to determine the influence of accounting information systems and internal control on the quality of financial reports at PT. Perkebunan Nusantara IV Regional 1. This research uses primary data. Primary data is obtained from answers to a series of statements in the form of a questionnaire to PT employees. Perkebunan Nusantara IV Regional 1, totaling 60 respondents. The sampling technique in this study used the Saturated Sampling Technique, where all the population in this study was sampled. In this study, the population and samples taken were all employees of PTPN IV in the finance department, totaling 60 people. This research uses multiple linear regression analysis techniques. Based on the results of partial testing of the Accounting Information System on the Quality of Financial Reports, the calculated t value was 6.023 > 1.672 and had a significant number of 0.011 < 0.05. Based on the results of partial testing of the Internal Control variable on the Quality of Financial Reports, the calculated t value was 2.699 > 1.672 and had a significant number of 0.000 < 0.05. When compared with the Ftable value, Fcount > Ftable, or 16.520 > 3.092, thus it can be concluded that all independent variables (X1 and X2) simultaneously influence the dependent variable (Y).